2023
DOI: 10.1007/s11229-023-04045-1
|View full text |Cite|
|
Sign up to set email alerts
|

Against a normative asymmetry between near- and future-bias

Abstract: Empirical evidence shows that people have multiple time-biases. One is near-bias; another is future-bias. Philosophical theorising about these biases often proceeds on two assumptions. First, that the two biases are independent: that they are explained by different factors (the independence assumption). Second, that there is a normative asymmetry between the two biases: one is rationally impermissible (near-bias) and the other rationally permissible (future-bias). The former assumption at least partly feeds in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
3
2
Order By: Relevance
“…Unlike Latham et al (2023), however, we did not find an association between futurebias and near-bias (at least, once people who had no preference were removed from the sample). This is puzzling given that Latham et al ( 2023) found a moderately strong association.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…Unlike Latham et al (2023), however, we did not find an association between futurebias and near-bias (at least, once people who had no preference were removed from the sample). This is puzzling given that Latham et al ( 2023) found a moderately strong association.…”
Section: Discussioncontrasting
confidence: 85%
“…One potential explanation for this is the difference in the relative proportions of people reporting being future-biased and near-biased across the two studies. Latham et al (2023) found a larger proportion of people reporting both futurebiased and near-biased preferences than we did in the current study. The difference in proportions may, in turn, be explicable in terms of the differences between the vignettes that participants saw.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Greene, Latham, Miller and Norton (2021) found that ~85% of participants were future-biased when it came to negative hedonic states of affairs such as pain. Latham, Miller and Norton (2023) found ~70%, Latham, Miller, Tarsney and Tierney (2021) found ~70%, Latham, Oh, Miller, Shpall and Yu (forthcoming) found ~63% while found 62%. Our results in this study are a little lower than most of these, though they were within the range reported by Latham, Miller, Norton and Tarsney. This suggests that the complexity of the setup may in fact have reduced future-biased preferences a little.…”
Section: 6mentioning
confidence: 90%